Review on Pharmacology and Phytochemistry of Cyperus rotundus L. - Muneesh Kumar; Manisha Rani; Bibekananda Meher (Current Research in Pharmaceutical Sciences, 2017)
Nowadays there is increasing interest of researchers to explore herbal drugs for health benefits of human as well as animals. Drugs which are obtained from natural sources are pharmacologically potent and have low or no side effects for use in preventive medicine. Cyperus rotundus L. is commonly known as nagarmotha, motha in local languages. It is available all over the country. Cyperus rotundus is having some reported activities like antidiabetic, hypolipidemic, hepatoprotective and antimicrobial properties. It contains flavonoids, tannins, glycosides, monoterpenes, sesquiterpenes, sitosterol, alkaloids saponins, terpenoids, essential oils, starch, carbohydrates, protein, separated amino acids and different secondary metabolites. Considering the growing interest in the field of plant drugs assessing different pharmacological activities. In this review we are discussing about the therapeutic potential and chemical constituents of Cyperus rotundus.